2007
DOI: 10.1063/1.2770652
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature ordering of (001) granular FePt films by inserting ultrathin SiO2 layers

Abstract: L 1 0 granular FePt–SiO2 films with a (001) preferred orientation and well-separated grains of 5.14nm were obtained by depositing atomic-scale Fe∕Pt∕SiO2 multilayers (MLs) on glass substrates and subsequently annealing MLs at a temperature of 350°C. Large out-of-plane coercivity of 7700Oe and a high ordering factor of 0.83 were achieved. Alternate atomic-scale depositions promoted the formation of (001) textures. Furthermore, because of the low surface energy of SiO2 layers, SiO2 tended to diffuse into grain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 21 publications
0
41
0
1
Order By: Relevance
“…In the L10 phase, the atomic arrangement of Fe and Pt along c axis is like Fe/Pt multilayers. Since the perpendicular anisotropy of FePt films is strongly associated with the formation of the (001)-oriented L10 phase, the fabrication of FePt films by annealing Fe/Pt multilayers could not only effectively decrease the diffusion length of Fe and Pt atoms into L10 structure but also promote the perpendicular anisotropy [21]. On the other hand, there is very large interface energy in Fe/Pt multilayers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the L10 phase, the atomic arrangement of Fe and Pt along c axis is like Fe/Pt multilayers. Since the perpendicular anisotropy of FePt films is strongly associated with the formation of the (001)-oriented L10 phase, the fabrication of FePt films by annealing Fe/Pt multilayers could not only effectively decrease the diffusion length of Fe and Pt atoms into L10 structure but also promote the perpendicular anisotropy [21]. On the other hand, there is very large interface energy in Fe/Pt multilayers.…”
Section: Resultsmentioning
confidence: 99%
“…We can see that the (001) and (002) superlattice peak positions of the films with Cu doping are higher than that of the FePt films without Cu doping. The previous research indicated that Cu in ordered FePtCu alloy is substituted into the Fe site in the L10 ordered FePt alloy; that is, the Cu is in the Fe plane of the L10 ordered FePt alloy through first-principle band calculations and ultraviolet photoelectron spectroscopy experiment [21]. The radius of Cu atom is smaller than that of Fe atom, which leads to decrease in the (001) plane spacing and the superlattice diffraction peaks of ordered phase shifted to the higher angles [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hetero-epitaxial L1 0 FePt films were fabricated on single crystal substrate at high deposited temperature, for example, MgO substrate, or MgO, Cr/Pt, CrRu intermediate layer or Si substrate with suitable underlayer such as TiN, Ag [6][7][8][9]. The (0 0 l) textured (Pt/Fe) x films were typically prepared on amorphous substrates such as SiO 2 /Si, glass and subsequently annealing by rapid thermal process (RTP) [10,11]. The alternated deposition of (Pt/Fe) multilayer on MgO or glass substrate has been reported widely due to the lower ordering temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high energy barrier, the transformation into the ordered L1 0 phase needs a subsequent annealing at temperatures above 500 8C to obtain the tetragonal distortion giving the strong ferromagnetic L1 0 phase. [9] In previous studies, we reported of low transition temperatures (T $ 350 8C) achieved using a special magnetron sputtering setup characterized by high amount of energetic atoms involved in the deposition that creates vacancies into the as-deposited films. [10] In this paper, we describe the fabrication of granular L1 0 -FePt/Ag films grown on SiO 2 (500 nm)/Si (001) substrates by means of sequential deposition of FePt and Ag at 400 8C.…”
mentioning
confidence: 99%